Cardio- and cerebrovascular responses to the energy drink Red Bull in young adults: a randomized cross-over study. - Grasser, Erik; Yepuri, Gayathri; Dulloo, Abdul; Montani, Jean-Pierre (European Journal of Nutrition, 2014)
Purpose: Energy drinks are beverages containing vasoactive metabolites, usually a combination of caffeine, taurine, glucuronolactone and sugars. There are concerns about the safety of energy drinks with some countries banning their sales. We determined the acute effects of a popular energy drink, Red Bull, on cardiovascular and hemodynamic variables, cerebrovascular parameters and microvascular endothelial function. Methods: Twenty-five young non-obese and healthy subjects attended two experimental sessions on separate days according to a randomized crossover study design. During each session, primary measurements included beat-to-beat blood pressure measurements, impedance cardiography and transcranial Doppler measurements for at least 20 min baseline and for 2 h following the ingestion of either 355 mL of the energy drink or 355 mL of tap water; the endothelial function test was performed before and two hours after either drink. Results: Unlike the water control load, Red Bull consumption led to increases in both systolic and diastolic blood pressure ( p < 0.005), associated with increased heart rate and cardiac output ( p < 0.05), with no significant changes in total peripheral resistance and without diminished endothelial response to acetylcholine; consequently, double product (reflecting myocardial load) was increased ( p < 0.005). Red Bull consumption also led to increases in cerebrovascular resistance and breathing frequency ( p < 0.005), as well as to decreases in cerebral blood flow velocity ( p < 0.005) and end-tidal carbon dioxide ( p < 0.005). Conclusion: Our results show an overall negative hemodynamic profile in response to ingestion of the energy drink Red Bull, in particular an elevated blood pressure and double product and a lower cerebral blood flow velocity.